Restricted cubic spline model analysis of the association between anal fistula and anorectal abscess incidence and body mass index - Ye, Sangyu; Huang, Zichen; Zheng, Lihua; Shi, Yuying; Zhi, Congcong; Liu, Ningyuan; Cheng, Yicheng (Frontiers in Surgery, 2024)
The epidemiological profile of anal fistula and anorectal abscess has not been well studied. Based on the results of a retrospective cross-sectional survey, we aimed to investigate the potential influential factors associated with anal fistula and anorectal abscess.We conducted a retrospective analysis of outpatients who visited the proctology department at China-Japan Friendship Hospital between January 2017 and May 2022. A comprehensive questionnaire was designed to collect potential influential factors, and according to formal anorectal examination and the corresponding diagnostic criteria, all the participants were divided into patients with anal fistula or perianal abscess and healthy control group. Multiple logistic regression was used to identify factors in significant association with anal fistula and perianal abscess. Additionally, we combined restricted cubic spline regression to examine the dose-response relationship between factors and the risk of developing anal fistula or anorectal abscess.The present study included 1223 participants, including 1018 males and 206 females, with 275 anal fistulas, 184 anorectal abscesses, and 765 healthy controls. We found no statistically significant differences between patients and controls in basic information and preoperative assessment of life factors, except for body mass index. It was indicated that people with overweight or obesity were more prone to anal fistula (OR overweight=1.35, 95% CI: 1.00-1.82, P=0.047; OR obesity=3.44, 95% CI: 2.26-5.26, P<0.001) or anorectal abscess (OR overweight=1.41, 95% CI: 1.00-1.99, P=0.05; OR obesity: 2.24, 95% CI: 1.37-3.67, P=0.001) than normal-weight individuals. The dose-response research indicated the J-shaped trend between the ascending BMI levels and the higher risk of suffering from anal fistula and anorectal abscess.Our findings indicate that overweight and obesity are risk factors for anal fistula and anorectal abscess, which plays a role in the prevention of anorectal diseases. This provides some theoretical basis for clinicians to provide health education to their patients.